Variação, estilo, atitude e percepção linguística: o caso das laterais /ʎ/ e /l/ no falar paraibano - Freire, Josenildo Barbosa (2016)
This thesis analyzes the social and stylistic variation of the side net /ʎ/ and /l/ the Portuguese of Brazil, as in the realizations of /ʎ / ~ [l, j, Ø] and those of / l / ~ [w, j, Ø, ł], and at the same time, examines the aspects of evaluation, attitude and language perception linked to them. The examined speaking community is the city of Jacaraú in Paraíba state, located in the middle region of Paraibana Forest, northern coastline of Paraiba. The theoretical contributions that underlie the analysis come from the Sociolinguistics Quantitative Labovian inspiration (Labov, 1963, 1966, 2008 [1972], 2001) and research of Campbell-Kibler (2006) and Clopper & Pisoni (2005), addressing language issues highlighting the cognitive ability of speakers / listeners to indicate with some precision, sociodialetais differences and, in Garrett contributions, Coupland & Williams (2003), Oppenheim (1982), Sarnoff (1970) and Bisinoto (2000) that show the procedural aspect and sociolinguistic related to attitudes and language assessment. Thus, it was been a socially stratified corpus of spoken language of 36 (thirty six) informants speaking community searched; Also, these sociolinguistic interviews were described and specifically analyzed the Language Module, checking how the speakers surveyed assess their own speech and that of others, and later in the same community, an evaluation instrument was-applied, attitude and language perception. In this sense, we tried to study the phenomena described herein considering the objective dimension, by taking the linguistic fact itself - /ʎ/ and /l/ and its linguistic variants, as well as the subjective dimension, considering the speaker - its characteristics sociocultural and subjective correlates. In general, quantitative analysis demonstrated that the use of side segments /ʎ/ and /l/, besides constituting a social process variation, too, are stylistic phenomena, but of different nature which is led hence perform the evaluation test, attitude and language perception involving only /ʎ/ and its variant forms. With regard to the Language Module analysis of the findings, it could be verified that the results point to the central role of informers in the processes discussed here, revealing aspects of the evaluative dimensions, representing, attitudinal and social significance; and finally, regarding the results arising from the application of the instrument, especially from subjective reactions collected, have resulted in two sociodialetais usage patterns: marked socially x not socially marked and indicated by different linguistic variants, respectively, represented by [l, j, Ø] to the Northeast / rural and [ʎ] related to the Northeast / urban; and also made it possible to propose a gradational scale of acceptance (EGA, see Figure 7); also suggest that the use of /ʎ/ and its variants are independent of the informant and sex were assessed as speakers 'polite', now they were associated with talking friendly, confident, family; now, however, as the linguistic forms of low social prestige, were linked to professionals who do several handy works and recognized for use in the context of minor stylistic monitoring, while [ʎ] was related to the status of speakers, for example, engineers and teachers, for use in more formal situations. About age, these variants were perceived as both youth and adults, and the experiment recorded on the one hand, very high rejection rates the forms [l, j, Ø], which ranged from 81% to 93% of rejection and, on the other hand, indicated positive results about the use of [ʎ]: 79% approval.